Influence of maternity leave on exclusive breastfeeding - Fernanda R. Monteiro; Gabriela dos S. Buccini; Sônia I. Venâncio; Teresa H.M. da Costa (Elsevier, 2017)
Objectives: To describe the profile of women with children aged under 4 months living in the Brazilian state capitals and in the Federal District according to their working status and to analyze the influence of maternity leave on exclusive breastfeeding (EBF) among working women. Methods: This was a cross-sectional study with data extracted from the II National Maternal Breastfeeding Prevalence Survey carried out in 2008. Initially, a descriptive analysis of the profile of 12,794 women was performed, according to their working status and maternity leave and the frequency of maternity leave in the Brazilian regions and capitals. The study used a multiple model to identify the influence of maternity leave on EBF interruption, including 3766 women who declared they were working and were on maternity leave at the time of the interview. The outcome assessed in the study was the interruption of the EBF, classified by the WHO. Results: Regarding the working status of the mothers, 63.4% did not work outside of their homes and among those who worked, 69.8% were on maternity leave. The largest prevalence among workers was of women older than 35 years of age, with more than 12 years of schooling, primiparous and from the Southeast and South regions. The lack of maternity leave increased by 23% the chance of EBF interruption. Conclusion: Maternity leave contributed to increase the prevalence of EBF in the Brazilian states capitals, supporting the importance of increasing the maternity leave period from four to six months. Resumo: Objetivos: Descrever perfil das mulheres com filhos menores de 4 meses residentes nas capitais brasileiras e no Distrito Federal segundo situação de trabalho e analisar a influência da licença-maternidade sobre o aleitamento materno exclusivo entre as mulheres trabalhadoras. Métodos: Trata-se de um estudo transversal com dados extraídos da II Pesquisa Nacional de Prevalência do Aleitamento Materno realizada em 2008. Inicialmente foi realizada análise descritiva do perfil das 10.995 mulheres participantes do estudo segundo situação de trabalho e de licença-maternidade, bem como a frequência de licença-maternidade nas regiões brasileiras e capitais. Em seguida, para identificar a influência da licença-maternidade na interrupção do aleitamento materno exclusivo, realizou-se modelo múltiplo, onde foram incluídas 3.766 mulheres que declararam trabalhar e estar em licença-maternidade no momento da entrevista. O desfecho adotado no estudo foi a interrupção do aleitamento materno exclusivo, classificado de acordo com a definição da Organização Mundial da Saúde. Resultados: Em relação à situação de trabalho, 63,4% das mães entrevistadas no Brasil não trabalhavam fora do lar e dentre as que trabalhavam fora, 69,8% usufruíam da licença-maternidade. Verificou-se maior concentração de mulheres que trabalhavam fora entre aquelas com mais de 35 anos, mais de 12 anos de escolaridade, primíparas, das regiões Sudeste e Sul. Para as mulheres que não estavam em licença-maternidade, após ajuste para todas as co-variáveis, houve um aumento da prevalência de interrupção do aleitamento materno exclusivo (RP [IC95%] ajustada 1,23 [1,11 - 1,37]). Conclusão: Verificou-se que as mulheres que não estavam em licença-maternidade de 120 dias apresentaram maior prevalência de interrupção do aleitamento materno exclusivo nas capitais brasileiras e Distrito Federal, no ano de 2008, reforçando a importância da ampliação da licença-maternidade para 6 meses. Keywords: Exclusive breastfeeding, Maternity leave, Women and work, Palavras-chave: Aleitamento materno exclusivo, Licença-maternidade, Mulher e trabalho